A GENERALLY APPLICABLE METHOD FOR THE MEASUREMENT OF HETEROGENEOUS RATE CONSTANTS OF REACTIONS OCCURRING AT THE SOLID LIQUID INTERFACE - Unwin, P; Barwise, A; Compton, R (1989)
The development and proving of a novel, generally applicable technique for the deduction of heterogeneous kinetics are described. The experiment consists of a flow cell in the form of a channel electrode, with the solid substrate of interest forming part of one wall of the cell, through which the reactant is flowed. An amperometric detector electrode is located immediately downstream of the substrate and used to give a measure of the extent of the reaction under steady-state conditions. Analytical theory is derived relating the observed current at the detector electrode to the heterogeneous rate constant for the reaction, the cell geometry, and the solution flow rate. The design of a suitable cell by which such measurements may be made is presented, and the use of the technique is illustrated by reference to the reaction of acidified bromine water with a cloth dyed with Direct Red 80. Good agreement is found between theory and experiment. It is suggested that the method is readily generalized through the use of either potentiometric or nonelectrochemical methods of detection. © 1989.